Repercussões do posicionamento corporal no estado fisiológico e comportamental de recém-nascido pré-termo - Santos, Alessandra Madalena Garcia (2017)
Preterm birth provides modifications for both the life of the Newborn (NB) as family. Among these changes has been hospitalization in Neonatal Intensive Care Units (NICU) due to the immaturity of organs and systems, generating the need for treatment and intensive care. Because of hospitalization, complications may occur or biological, psychological and social changes to the Newborn Preterm (PTN), which can lead to changes in Neuropsychomotor Development (DNPM). One way to minimize these complications is through proper body positioning premature procedure performed during routine care team in a NICU. However, a gap is evident as regards the PTN response during positioning correlating different positions during hospitalization, as well as the comparison between standard protocols and procedures routine in the NICU. Therefore, the main objective of this research was to compare the physiological, behavioral and pain responses presented by PTN subjected to a Standard Operating Procedure (SOP) body position with those in routine positioning of the NICU. Quantitative study, prospective, randomized clinical trial type, conducted from July 2015 to March 2016 with 30 preterm infants admitted to the NICU of a teaching hospital of the West of Paraná. The subjects were randomly separated into Unit Routine Decubitus group (URD) and Intervention Group (GI), on which it was subjected to previously validated positioning protocol and proposed in 2015. The variables analyzed in the study were: physiological characteristics (respiratory rate, heart rate and oxygen saturation); behavior (measured by the Scale of Brazelton Modified - EBM) and pain (scale verified by the Neonatal Infant Pain Scale - NIPS). The study sample consisted of preterm infants with gestational age for both groups predominantly between 28 and 32 weeks and birth weight between 1001 and 1499 grams, characterizing the sample as very premature and very low birth weight. Regarding the physiological variables it was observed throughout the procedure that the heart rate in URD remained lower compared to the values submitted by the IG; Respiratory Rate (RR) in the URD was higher when compared to IG and oxygen peripheral saturation values remained stable in both groups. The PTN behavior, by EBM and pain by NIPS, showed similar scores in both groups before the start of the procedure, however, significantly lower in IG during the intervention. It is pointed out then that the positioning SOP provided decrease in RR in scores of pain and behavior scales, when compared to the URD. It is believed that a standardized position in the long term hospitalization contribute to the proper DNPM.